If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4m+17=-(4-m)
We simplify the equation to the form, which is simple to understand
4m+17=-(4-m)
Remove unnecessary parentheses
4m+17=-4+1m
We move all terms containing m to the left and all other terms to the right.
+4m-1m=-4-17
We simplify left and right side of the equation.
+3m=-21
We divide both sides of the equation by 3 to get m.
m=-7
| 5.5=-2 | | h(t)=30t-2t^3 | | w+6=6(w-6) | | 12+(7+32)= | | 9/11/9= | | -4(x+3)=36 | | 7z=72 | | 5x-10/6x-6 | | 10x/12=-28 | | 24n+18=4n-2 | | 7/3x=77/4 | | 4j+6j=8.6 | | -4s-5+6-3s= | | -9-2x=17-x | | 3x+27=4.5x | | 90=(x+2)(5x) | | Y=-.25x+1 | | -37=12+-85 | | DX(t)/dt | | 12x-93=3x+105 | | (X^2)-((y^2)/35)=1 | | 0.33(x-16)=-2(x-3)+4 | | 2(3x-2)-2=2(x-2)+6 | | -8(3x+1)=8x-7(6x+5) | | -r-5(2r+2)=-76 | | 5/7x.25 | | X=3(6y-8) | | 2[2y+2]-5y=1 | | u-2=5 | | 90+x=5x | | n=30-25 | | 8t=3[t+55] |